ANALYSIS OF THE EFFECT OF HOT FLUID FLOW SPEED VARIATIONS ON POTATO CHIPS DRYING CAPACITY USING LPG GAS - Karyasa, Tungga Bimadi; Syamsuri, S (TURBO [Tulisan Riset Berbasis Online], 2025)
Some of the potato chips circulating in the community contain carbohydrates and have high oil absorption capacity. This slicing or slicing stage affects the level of uniformity of the potatoes during the oven, because during the oven the potato slices that are not uniform will cause case hardening and if they are too thin they will easily burn. Then cool, slice and dry until the water reaches 10%. To find out what percentage of water content is in potatoes so that these potatoes can be consumed properly, this research was carried out. In this research, the following research variations were carried out; the speed of the incoming air flow is 3.8 m/s, 4.2 m/s, and 4.5 m/s. The results of this research are that the greater the speed of hot air, the greater the resulting temperature. After testing for 30 minutes and with variations in air speed of 4.5 m/second, the potato weight was 505 grams. LPG fuel is more efficient than other fuels.